Acute Toxicity and the Effect of Andrographolide on Porphyromonas gingivalis-Induced Hyperlipidemia in Rats. (6th June 2013) - Al Batran, Rami; Al-Bayaty, Fouad; Al-Obaidi, Mazen M. Jamil; Abdulla, Mahmood A.
Abstract : The aim of the current study is to evaluate the effect of andrographolide on hyperlipidemia induced by Porphyromonas gingivalis in rats. Thirty male Sprague Dawley (SD) rats were divided into five groups as follows: group 1 (vehicle) and four experimental groups (groups 2, 3, 4, and 5) were challenged orally with P. gingivalis ATCC 33277 (0.2 mL of 1.5 × 10 12 bacterial cells/mL in 2% carboxymethylcellulose (CMC) with phosphate-buffered saline (PBS)) five times a week for one month to induce hyperlipidemia. Then, group 3 received a standard oral treatment with simvastatin 100 mg/kg, and groups 4 and 5 received oral treatment with andrographolide 20 mg/kg and 10 mg/kg, respectively, for another month. The results showed that total cholesterol (TC), low-density lipoprotein (LDL-C), and triglycerides (TG) were reduced significantly in groups treated with andrographolide. The malondialdehyde (MDA) level was low in treated groups, while antioxidant enzymes, superoxide dismutase (SOD), and glutathione peroxidase (GPx) were significantly increased in these groups (P < 0.05 ). Liver tissues of the groups treated with andrographolide reduce the accumulation of lipid droplets in hepatic tissue cells. An acute toxicity test did not show any toxicological symptoms in rats.